An interprofessional early childhood training program: speech-language pathology and music therapy student outcomes and reflections. Issue 6 (1st November 2020) - Cassidy, Corey; Winter, Patricia; Cumbia, Skyler
ABSTRACT: Speech-Language Pathologists (SLP) and Music Therapists (MT) frequently work together in a wide variety of healthcare settings. This collaboration has tremendous potential for providing effective client-focused care and is in line with best practices for both professions. There are tensions that may arise within these collaborations, however, as each profession attends to their own scope of practice and works to understand the boundaries between each treatment modality. One way to address these essential professional relationships and potential tensions is to embed opportunities for SLP and MT students to co-treat within their educational training programs. This report outlines a preliminary evaluation of SLP and MT student readiness for interprofessional practice and their unique experiences as co-therapists within a fully collaborative clinical setting for young children with speech and language disorders. Through a mixed method program evaluation that included the Readiness for Interprofessional Learning Scale and focus group interviews, SLP and MT students explored their experiences with IP service provision, and their experiences as students in this type of learning environment.